Back Cover: Parametric Type‐II Dirac Photonic Lattices (Adv. Quantum Technol. 7/2020). Issue 7 (6th July 2020) - Jin, Kaichao; Zhong, Hua; Li, Yongdong; Ye, Fangwei; Zhang, Yanpeng; Li, Fuli; Liu, Chunliang; Zhang, Yiqi
Abstract : Different from previous investigations, Yiqi Zhang and co‐workers (see article number 2000015 ) develop a new kind of Dirac photonic lattice that possesses type‐II Dirac cones in the band structure intrinsically. In other words, the appearance of the type‐II Dirac cone is only dependent on the spatial symmetry of the photonic lattice. Conical diffraction and Klein tunneling in this novel type‐II Dirac photonic lattice are discussed in detail.